ANTI-CORRUPTION PROGRAMS IN DIRECTORATE GENERAL OF TAXES (DGT) IN INDONESIA - Yudisatria, Aria (Journal of Governance and Administrative Issues, 2022)
Indonesia's Directorate General of Taxes (DGT) has undergone significant bureaucratic reforms since 2002 to combat systemic corruption within its tax administration. These reforms aimed to improve transparency, accountability, and internal control mechanisms. This paper examines the effectiveness of various anti-corruption programs implemented by the DGT, identifying both successful initiatives and areas of inefficiency. Effective programs include the establishment of the Large Taxpayer Office (LTO), the wage increase and remuneration program, and efforts to transform organizational culture. However, challenges remain, particularly concerning the whistleblowing system (WBS) and the internal control bodies at tax offices, which face issues such as limited transparency, inadequate protection for whistleblowers, and cultural barriers to reporting corruption. The study concludes that while the reforms have generally been successful in reducing corruption, further improvements are needed in strengthening internal controls, addressing cultural obstacles, and enhancing the transparency and protection mechanisms in whistleblowing programs.